1997
DOI: 10.1055/s-0038-1655939
|View full text |Cite
|
Sign up to set email alerts
|

Anticardiolipin Antibodies and Recurrent Thromboembolism

Abstract: We read with interest the letter from Prandoni et al. (1) reporting the high risk of thromboembolic recurrence after interruption of oral anticoagulants in patients with antiphospholipid antibodies suffering a first episode of venous thrombosis. The authors obtained these results in patients with lupus anticoagulant alone, and in patients with both lupus anticoagulant and anticardiolipin antibodies. We have found similar results in patients with anticardiolipin antibodies alone suffering an episode of venous t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
5

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 0 publications
2
34
0
5
Order By: Relevance
“…As shown in Table 1, at least 10 different screening and confirmatory assays were used either alone or in various combinations to detect lupus anticoagulants. Three studies 26,32,36 did not provide enough information about the laboratory methods used to diagnose lupus anticoagulants. Three studies 32,34,36 did not give laboratory details about anticardiolipin antibody detection.…”
Section: Literature Search Strategy and Articles Retrievedmentioning
confidence: 99%
“…As shown in Table 1, at least 10 different screening and confirmatory assays were used either alone or in various combinations to detect lupus anticoagulants. Three studies 26,32,36 did not provide enough information about the laboratory methods used to diagnose lupus anticoagulants. Three studies 32,34,36 did not give laboratory details about anticardiolipin antibody detection.…”
Section: Literature Search Strategy and Articles Retrievedmentioning
confidence: 99%
“…207,209 These recommendations are based on results of randomized trials 207 that demonstrated that oral anticoagulants effectively prevent recurrent venous thrombosis (risk reduction Ͼ90%), that treatment for 6 months is more effective than treatment for 6 weeks, 206 and that treatment for 2 years is more effective than treatment for 3 months. 208 …”
Section: Treatment Of Deep Venous Thrombosis or Pulmonary Embolismmentioning
confidence: 99%
“…There is a high risk of recurrence after discontinuation of oral anticoagulant therapy, [19][20][21][22][23] and in the present patient pulmonary embolism recurred 10 months after cessation of warfarin. Therefore, long-term anticoagulant therapy is thought to be necessary.…”
Section: Discussionmentioning
confidence: 53%
“…Lifelong treatment with oral anticoagulants with a target INR of 3.0 or more has been recommended, based on data from 3 retrospective studies, 19 but several recent reports have suggested that many patients with APS can be treated with conventional doses of warfarin. [21][22][23]25 The risk of high-intensity anticoagulant therapy in patients with APS has also been reported. 26 The present patient's course has been uneventful for 14 months on a target INR of 2.0-2.5 after the most recent episode.…”
Section: Discussionmentioning
confidence: 98%